Pengelolaan Program Denpasar Mantap Kesehatan Masyarakat di Kota Denpasar dalam Perspektif Dynamic Governance - Ni Putu Dinda Kalpika Putri; Carollina Augi Widya Putri (Journal of Contemporary Public Administration, 2023)
Good governance must be built so that the ideals of the Indonesian people contained in the 1945 Constitution of the Republic of Indonesia in the fourth paragraph can be realized. To make this happen, the Government of Indonesia is focusing on changes to 8 main areas contained in the 2010-2025 Bureaucratic Reform Grand Design which are devoted to excellent service to the community. The government is expected to be able to implement dynamic governance, according to the changing times but not ignoring the needs of the community. However, in carrying out this governance, of course there is an obstacle, especially in the health sector services at the Denpasar City Health Office. The mobility of the population is quite high and the pre-hospital services available to the people of Denpasar City are quite limited so to overcome this, the Denpasar City Government created a Health program, namely Denpasar Mantap Community Health or DAMAKESMAS. The program, which is coordinated by the Denpasar City Health Office, collaborates with the Denpasar City BPBD and the Denpasar City Communications, Informatics and Statistics Office. This research was conducted with the aim of analyzing and observing DAMAKESMAS management from dynamic governance. This type of research is descriptive research with a qualitative approach. Data collection techniques used are observation, interviews and documentation. Based on this research showing that the management of DAMAKESMAS is from a dynamic governance approach, the researchers found that the Denpasar City Government has been thinking ahead to improve health services. However, in its management there are obstacles that the government must rethink. To create complexity from managing this program, it must be run with cross-thinking.